The Role of Purchase Intention in Mediating Celebrity Endorser, Ewom, and Brand Image on Purchase Decision - Novriyanti, Rara; Ali, Suprihatin; Adistya, Diang (Journal of Business Management and Economic Development, 2025)
In the globalization era, increasing product competition compels producers to prioritize consumer needs. Wardah emerges as a cosmetic brand that addresses these demands through its commitment to quality and adherence to halal standards. This study aims to explore the role of Purchase Intention as a mediating variable in the relationship between Celebrity Endorser, Ewom, and Brand Image on Purchase Decision. Employing a quantitative approach with an explanatory research design, the study targeted Wardah cosmetic consumers residing in Bandar Lampung. A purposive sampling technique was applied, involving 100 respondents using a Likert-scale questionnaire. Data analysis was conducted through SEM using SmartPLS 4.0 software. The findings reveal that brand image significantly influences purchase intention, while purchase intention fully mediates its impact on purchase decisions. Conversely, celebrity endorsers and ewom do not significantly affect purchase intention. These results underscore the critical role of enhancing brand image to boost consumer purchasing intentions and decisions. Accordingly, it is recommended that Wardah optimize the use of suitable celebrity endorsers and leverage interactive platforms such as TikTok to reinforce its brand image and drive purchase decisions. Future researchers are encouraged to broaden the scope of variables and incorporate comparative analyses to enrich and extend the applicability of the study's findings.